2013
DOI: 10.4236/ojmp.2013.23015
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation and Attempts during Middle Childhood: Associations with Subjective Quality of Life and Depression

Abstract: Background: Confronted to the increasing suicide rate in children, clinicians have to better understand and predict suicide-related behaviours (SRBs) in children with and without depressive symptoms. Aims: To investigate associations among suicidal tendencies (thoughts and/or attempts), depression and children's perceptions of subjective quality of life. Methods: This was a cross-sectional study of 157 children of 6-13-year-old. Results: Children who attempted or thought of suicide reported goodless subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The association between antisocial personality disorder and sudden violent death is consistent with previous research (Coffey et al, ; Repo‐Tiihonen et al, ). Similar to previous research (Bourdet‐Loubére, & Raynaud, ; Brent, Perper, Goldstein, et al, ; Cheng et al, ; Eapen & Crncec, ; Runeson, ; Williams, O'Connor, Eder, & Whitlock, ), we found an association between depression and suicide. Depression spectrum disorder was the largest diagnostic category in the suicide group (67% of cases), thus indicating that depression covaries with many other risk factors for suicide (Berman, Jobes, & Silverman, ; Lewinsohn et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…The association between antisocial personality disorder and sudden violent death is consistent with previous research (Coffey et al, ; Repo‐Tiihonen et al, ). Similar to previous research (Bourdet‐Loubére, & Raynaud, ; Brent, Perper, Goldstein, et al, ; Cheng et al, ; Eapen & Crncec, ; Runeson, ; Williams, O'Connor, Eder, & Whitlock, ), we found an association between depression and suicide. Depression spectrum disorder was the largest diagnostic category in the suicide group (67% of cases), thus indicating that depression covaries with many other risk factors for suicide (Berman, Jobes, & Silverman, ; Lewinsohn et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Known risk factors for suicidality among children, adolescents, and young adults include early neuroticism related to later depression, anxiety, substance abuse and conduct disorder, family problems, loss, and disturbed or insecure attachments in childhood, lack of parental care and maternal overprotection, stressful life events and risk behaviors (Fergusson, Woodward, & Horwood, 2000; Goschin, Briggs, Blanco-Lutzen, Cohen, & Galynker, 2013; King et al, 2001; Shiner, Scourfield, Fincham, & Langer, 2009). In the ages 6 to 13, suicide-related behaviors were associated with depressive symptoms and low perceived quality of life (Bourdet-Loubére & Raynaud, 2013).…”
mentioning
confidence: 99%